2009
DOI: 10.1534/genetics.109.108472
|View full text |Cite
|
Sign up to set email alerts
|

Removal of the Bloom Syndrome DNA Helicase Extends the Utility of Imprecise Transposon Excision for Making Null Mutations in Drosophila

Abstract: Transposable elements are frequently used in Drosophila melanogaster for imprecise excision screens to delete genes of interest. However, these screens are highly variable in the number and size of deletions that are recovered. Here, we show that conducting excision screens in mus309 mutant flies that lack DmBlm, the Drosophila ortholog of the Bloom syndrome protein, increases the percentage and overall size of flanking deletions recovered after excision of either P or Minos elements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 42 publications
0
20
0
Order By: Relevance
“…The Minos element was remobilized by crossing Mi(ET1)CG17350 MB01546 flies with P{hsILMiT} flies that provide a Minos transposase source driven by a heat-shock promoter. To improve deletion rate, we used a genetic background carrying a mutation of the mus309 gene, which increases both the number and size of the flanking genomic DNA deletions induced by the excision of Minos elements (Witsell et al, 2009). The mus309 gene encodes a DNA helicase involved in homology-directed repairs of double-stand breaks that typically occur after transposon excision.…”
Section: Fon Excisionsmentioning
confidence: 99%
“…The Minos element was remobilized by crossing Mi(ET1)CG17350 MB01546 flies with P{hsILMiT} flies that provide a Minos transposase source driven by a heat-shock promoter. To improve deletion rate, we used a genetic background carrying a mutation of the mus309 gene, which increases both the number and size of the flanking genomic DNA deletions induced by the excision of Minos elements (Witsell et al, 2009). The mus309 gene encodes a DNA helicase involved in homology-directed repairs of double-stand breaks that typically occur after transposon excision.…”
Section: Fon Excisionsmentioning
confidence: 99%
“…It is estimated that the proportion ranges from 35 to 75% for all recovery events (Voelker et al, 1984;O'Brochta et al, 1991;Witsell et al, 2009). Considering that in certain cases we need to create a deletion of a specific size or in a precisely defined region to disrupt a given gene through imprecise excision, the frequency should be dramatically lower.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, besides inducing single P-element transposition, we can also induce simultaneous mobilization of multiple P-elements to delete the internal sequence (Parks et al, 2004). Additionally, Witsell et al (2009Witsell et al ( , 2010 recently demonstrated that it can increase the percentage of imprecise excision and overall size of flanking deletion during either P or Minos element transposition, when the transposition is performed in the mus309, which encodes DmBlm, a RecQ DNA helicase involved in DNA repair, mutant background. These approaches enhance the efficient desired deletion of large DNA fragment.…”
Section: Resultsmentioning
confidence: 99%
“…In our experiments, we found that 1.5–3.6% of excision events extended to a nearby polymorphic site. The frequency of such excisions can be increased by inhibiting the pairing between the transposable element chromosome and its homolog via a chromosome deficiency (14), or by screening in a mus 309 mutant background that lacks the Bloom syndrome helicase, thus increasing the frequency and size of the deletions generated from P -element and minos excisions (15). However, both these schemes involve considerable extra breeding.…”
Section: Resultsmentioning
confidence: 99%
“…The frequency of such imprecise events varies from locus to locus (1 in 5 to 1 in 100 excision events) (1,11), and the frequency of imprecise excision can be increased dramatically in some specific genetic backgrounds or by inhibiting pairing between the transposable element chromosome and its homolog (14,15). Flies carrying a visibly marked [e.g., white + ( w + )] transposable element inserted into or near a gene of interest are crossed with flies containing a stable source of transposase.…”
Section: Introductionmentioning
confidence: 99%